PERAN IBU RUMAH TANGGA DALAM MENINGKATKAN PEREKONOMIAN KELUARGA (STUDI KASUS: PENGRAJIN TENUN SARUNG HITAM DI DESA BONTO BAJI KECAMATAN KAJANG KABUPATEN BULUKUMBA) - Lisra Uliana; Muh. Said; Rusdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine 1) the characteristics of black sarong weaving (tope le’leng), 2) identify the supporting factors and obstacles faced by housewives as economic actors through black sarong weaving, and 3) analyze the role of housewives as weavers in improving family economic conditions in Bonto Baji Village, Bulukumba Regency. This study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews with artisan housewives and village officials, as well as documentation. The data analysis technique used in this study is thematic analysis.The research findings indicate that 1) The process of weaving black sarongs involves several traditional stages, including the preparation of raw materials (warp threads and natural dyes from tarung leaves), the dyeing process, thread winding (appaturung), pattern formation and thread arrangement (anggane), and finally weaving (attannung) using a traditional loom. 2) The main supporting factors are increased purchasing interest due to the symbolic value of the sarong as a cultural identity, price variations that cater to various segments, and a self-employed work system at home. Conversely, inhibiting factors include promotional strategies that remain conventional (word of mouth), the dual burden of domestic and economic roles, and age-related factors that reduce the physical productivity of artisans. 3) The role of housewives in Bonto Baji Village reflects the implementation of the Triple Role of Women (reproductive, productive, and social). Productive contributions through weaving provide significant additional income to meet children’s food and educational needs, thereby enhancing family well-being and economic stability.